Respon Pemberian Liquid Organic Biofertilizer Urin Kambing Terhadap Pertumbuhan Dan Hasil Kedelai (Glycine max L.) - Acep Atma Wijaya; Nugraha Dadan Ramdani (Fakultas Pertanian Universitas Majalengka, 2022)
Soybean (Glycine max L.) is one of the main food commodities after rice and corn. The need for soybeans in Indonesia is quite high. Soybeans are used as a basic ingredient for various processed foods such as tempeh, tofu, soy milk, tauco, snacks, and the soy sauce industry. Apart from being a food ingredient, soybeans are also used as industrial ingredients and animal feed. The high level of population consumption in Indonesia for soybeans and their processed products makes soybeans an ingredient sought by the community, therefore it is necessary to increase soybean productivity to meet domestic needs. One way to increase production while reducing inorganic fertilizers is the use of Liquid Organic Biofertilizer (LOB). This study aims to determine the effect of LOB on soybean growth and yield. This study used a non-factorial randomized block design (RBD) with six treatments with four replications. The treatments tested were: P0 = Without LOB, P1 = Concentration of 25 ml/l of water, P2 = Concentration of LOB 50 ml/l of water, P3 = Concentration of LOB 75 m/l of water, and P4 = Concentration of LOB 100 ml/l water, P5 = LOB concentration 125 ml/l water. The results showed that the application of Liquid Organic Biofertilizer of golden snails had a significant effect on plant height and number of leaves 2 weeks, 4 weeks and 6 weeks, while the number of branches and the number of root nodules was effective at 6 weeks.